Core–shell g-C3N4/Pt/TiO2 nanowires for simultaneous photocatalytic H2 evolution and RhB degradation under visible light irradiation. Issue 18 (14th August 2019) - Dou, Hailong; Qin, Yumei; Pan, Feng; Long, Dan; Rao, Xi; Xu, Guo Qin; Zhang, Yongping
Abstract : Core–shell structural diagram (a) and proposed photocatalytic mechanism (b) for the CN/Pt/TiO2 composite. Abstract : Core–shell g-C3 N4 /Pt/TiO2 nanowire structures were successfully synthesized through a facile two-step synthetic methodology, involving photodepositing Pt nanoparticles on the surface of TiO2 nanowires and subsequent growth of g-C3 N4 (CN) layers via thermal evaporation of urea. The as-prepared CN/Pt/TiO2 composites show a higher photocurrent density compared to CN/TiO2 . The CN/Pt/TiO2 photocatalysts exhibit an enhanced H2 evolution rate of 8.93 μmol h −1 under visible light irradiation, which is 1.25 times higher than that of CN/TiO2 (7.15 μmol h −1 ), while Pt/TiO2 and TiO2 nanowires do not show any visible light responses. Our experiments demonstrate for the first time that CN/Pt/TiO2 with a unique core–shell nanowire structure of semiconductor–metal–semiconductor enables concurrent hydrogen evolution through photo-induced water splitting and RhB degradation by photo-oxidation in the visible range. This result is probably attributable to the formation of a heterojunction and the Pt nanoclusters in CN/Pt/TiO2, facilitating the electron transfer from the LUMO of g-C3 N4 to that of TiO2 and generating different active sites upon photo-absorption in the CN layers. Our work provides a feasible way to obtain H2 while treating sewage using photocatalysis.